IMPROVEMENT OF TRANSPORTATION SERVICE MANAGEMENT THROUGH INTEGRATED INFORMATION SYSTEM - suhendra vmi, adi (Jurnal Studi Inovasi, 2025)
This research is about innovation in improving the management of transportation services through an integrated information system through Document Collection and Data Base Analysis of Transportation Services in Tulangbawang Barat Regency, Motor Vehicle Pre-Test (PUJI KEMO) in Bireuen Regency, Documentation of Activities with Marki (PENDAKI) in Empat Lawang Regency. , and a Website-Based Road Equipment Monitoring Information System (SI MANJA) in Pamekasan Regency. The innovation of Document Collection and Analysis of the Transportation Service Data Base is the compilation of the transportation service data base in the development of all socio-economic activities and the development of a city. PUJI KEMO innovation is an activity to check the technical requirements and test the roadworthiness of motorized vehicles visually. If the estimated vehicle does not meet the technical and testing requirements, the road is directed to be repaired prior to registration, so that it will minimize the number of vehicles that do not pass the test which causes the test card number sequence in the SIM-PKB application. PENDAKI Innovation (MARKI) is an application as a means of delivering activity documentation in the form of photos and videos. Not only does it contain camera features, MARKI contains some information including the day, date, time, coordinates, names of members in teams, names of activities and other information listed on photos or videos taken by the MARKI application. SI MANJA's innovation is a record that arises when maintenance or repairs are carried out on polishing, electrical installations and lighting components that become historical records that are stored digitally and can be accessed via internet connectivity. SI MANJA is a website based containing worksheets that have been done by technicians containing reports on work results, maintenance locations, dates of maintenance carried out, causes of damage, actions taken and replacement of spare parts. This study uses a qualitative approach research method. The data collection uses a literature review technique. Literature review is a systematic examination of critical scientific literature in analyzing, evaluating, and synthesizing research findings, theory, and practice. Literature review provides an overview of the development of a particular topic. The results of the innovation of Document Collection and Analysis of the Transportation Service Data Base are knowing the daily traffic data of motorized vehicles and the availability of documents or databases of transportation services at the Transportation Service Office of Tulang Bawang Barat Regency. The result of PUJI KEMO's innovation is the availability of Standard Operating Procedures (SOP) for regular motor vehicle testing before registering and paying the testing fee in Bireuen Regency. The result of PENDAKI (MARKI) innovation is the availability of the MARKI application as a photo and video recording during traffic engineering management activities on the road network in Empat Lawang Regency. The result of SI MANJA's innovation is the availability of technical data related to maintenance that has been carried out, both for public street lighting, traffic light and flash light, including the use of spare parts in Pamekasan Regency.